A unique C-type lectin, Ladderlectin, from large yellow croaker (Larimichthys crocea) is involved in bacterial cell membrane damage. Issue 136 (May 2023) - Tang, Xin; Zhu, Xingcheng; Liu, Xiande; Wang, Zhiyong; Zhang, Dongling
Abstract: Ladderlectin is unique C-type lectin because it has been so far found only in teleost fish. In this study, large yellow croaker ( Larimichthys crocea ) Ladderlecin ( LcLL ) sequence was identified and characterized. LcLL encodes a polypeptide of 186 amino acids that includes a signal peptide and a C-type lectin-like domains (CTLD) with two sugar-binding motifs of WSD and EPN. Tissues distribution analysis revealed that LcLL is a ubiquitous gene, with the highest expression in head kidney and gill. Subcellular localization showed that LcLL was in cytoplasm and nucleus of HEK 293T cells. Transcripts of LcLL were significantly up regulated after immune challenge with P. plecoglossicida . In contrast to this, a sharp down-regulation occurred after Scuticociliatida infection. Moreover, recombinant LcLL (rLcLL) was prepared and exhibited hemagglutination on L. crocea and N. albiflora erythrocytes in a Ca 2+ -dependent manner, which can be only inhibited by LPS. rLcLL showed a strong ability of binding to Gram + bacteria ( M. lysodeikticus, S. aureus, B. subtilis ) and Gram-bacteria ( P. plecoglossicida, E. coli, V. Vulnificus, V. harveyi, V. alginolyticus, V. parahaemolyticus. A. hydrophila, and E. tarda ), and could agglutinate all tested bacteria except for P. plecoglossicida . Further study showed that rLcLL promoted the gathered bacteria death through damaging cell membrane based on PI staining and SEM observation. However, rLcLL does neither kill bacteria directly nor have complement-activating activities. Altogether, these results demonstrated that LcLL played a vital role in L. crocea innate immune towards bacterial and parasitic challenge. Highlights: LcLL is in cytoplasm and nucleus of HEK 293T cells. rLcLL promotes the gathered bacteria death through damaging cell membrane. rLcLL exhibits a broad range of binding and agglutinating bacterial activity. rLcLL can only bind to LPS and hasn't binding ability to other sugars.